Analisis Prinsip Kehati-hatian dalam Fintech Peer to Peer Lending terhadap Pengguna berdasarkan Hukum Positif di Indonesia - Muhamad Marsandi Agustiarso (CV Rewang Rencang, 2025)
The rapid advancement of information technology, particularly within the financial sector through Financial Technology (Fintech) and Peer-to-Peer (P2P) Lending services, has significantly influenced society by delivering concrete benefits. Nonetheless, this progress also introduces inherent risks in its application. Consequently, the principle of prudence is crucial in the provision of P2P Lending services. This study aims to investigate the implementation of the prudential principle in Fintech P2P Lending by outlining its regulatory framework and examining the legal consequences arising from non-compliance with this principle. Employing a normative juridical methodology, the research utilizes both statutory and conceptual approaches. The prudential principle in P2P Lending services is governed by POJK No. 10/POJK.05/2022, which constitutes the legal basis for the operation of P2P Lending services. Additionally, PBI No. 19/12/PBI/2017 concerning the Implementation of Financial Technology mandates adherence to the prudential principle. Furthermore, Fintech P2P Lending providers must undergo a testing process within the Regulatory Sandbox to obtain a business license, as stipulated in POJK No. 3 of 2024 regarding the Implementation of Innovation in the Financial Technology Sector (ITSK). Legal repercussions for providers failing to comply with the prudential principle include administrative sanctions such as up to three written warnings, business operation restrictions, and ultimately, revocation of the business license.